Raman-Deuterium Isotope Probing for in-situ identification of antimicrobial resistant bacteria in Thames River. Issue 1 (December 2017) - Song, Yizhi; Cui, Li; López, José; Xu, Jiabao; Zhu, Yong-Guan; Thompson, Ian; Huang, Wei
Abstract The emergence and widespread distribution of antimicrobial resistant (AMR) bacteria has led to an increasing concern with respect to potential environmental and public health risks. Culture-independent and rapid identification of AMR bacteriain-situ in complex environments is important in understanding the role of viable but non-culturable and antibiotic persistent bacteria and in revealing potential pathogens without waiting for colony formation. In this study, a culture-independent and non-destructive phenotyping approach, so called Raman Deuterium Stable Isotope Probing (Raman-DIP), was developed to identify AMR bacteria in the River Thames. It is demonstrated that Raman-DIP was able to accurately identify resistant and susceptible bacteria within 24 hours. The work shows that, in the River Thames, the majority of the bacteria (76 ± 2%) were metabolically active, whilst AMR bacteria to carbenicillin, kanamycin and both two antibiotics were 35 ± 5%, 28 ± 3%, 25 ± 1% of the total bacterial population respectively. Raman activated cell ejection (RACE) was applied to isolate single AMR bacteria for the first time, linking AMR phenotype (reistance to antibiotics) and genotype (DNA sequence). The sequences of the RACE sorted cells indicate that they were potential human pathogensAeromonas sp., Stenotrophomonas sp. and an unculturable bacterium. This work demonstrates Raman-DIP and RACE are effective culture-independent approach for rapid identification of AMR bacteria at the single cell level in their natural conditions.